Standarised treatment regimens of tuberculosis - Kołaczkowska, Małgorzata (Przewodnik Lekarza/Guide for GPs, 2006)
Tuberculosis can be cured with the appropriate chemotherapy in over 90% of cases. On the basis of large number of controlled clinical trials the treatment guidelines have been issued by international bodies such as the World Health Organization and the International Union Against Tuberculosis and Lung Disease. These guidelines have been universally accepted. Success of tuberculosis treatment depends above all on the application of the standardized treatment regimens selected by the national tuberculosis programmes in accordance with the regimens recommended by WHO and IUATLD (Directly Observed Treatment Short-course). The article discusses the best recommended regimens of treatment and the toxicity of most often used drugs. Special attention is given to the treatment of tuberculosis in the patients with renal failure, hepatic diseases and pregnancy. The indications for corticosteroid use as adjunct therapy are presented.